Coptisine from Coptis chinensis blocks NLRP3 inflammasome activation by inhibiting caspase-1. (September 2019) - Wu, Jiasi; Luo, Yu; Jiang, Qing; Li, Sheng; Huang, Wenge; Xiang, Li; Liu, Deming; Hu, Yingfan; Wang, Ping; Lu, Xiaoxia; Zhang, Guolin; Wang, Fei; et al.
Graphical abstract: Coptisine prevents caspase-1 activity, leading to NLRP3 inflammasome disassembly and decreased secretion of IL-1β and IL-18. Coptisine also suppresses the interaction of both pro-caspase-1/RIP2 and caspase-1/MAL, which is followed by inhibition of NF-κB activation and blocking of NLRP3 inflammasome priming. Abstract: Inflammasome mediates the activation of caspase-1, which promotes the secretion of proinflammatory cytokines. In this work, we aimed to investigate whether natural compounds from a Traditional Chinese Medicine prescription called San-Huang-Xie-Xin-Tang exert its clinical efficacy by inhibiting inflammasome activation and the underlying mechanism. The inhibitory effects of compounds on caspase-1 were evaluated in recombinant expressed caspase-1 protein and macrophages. Molecular docking was conducted to examine the interaction between compounds and caspase-1. The effects of the compounds on pro-inflammatory cytokines were examined by enzyme-linked immunosorbent assay. The mechanism of the compounds on nucleotide oligomerization domain (NOD)-like receptor protein-3 (NLRP3) inflammasome activation was investigated in macrophages. The anti-inflammasome effects of compounds were examined in mice stimulated by lipopolysaccharide (LPS) and monosodium urate crystal (MSU). Coptisine was the most potent inhibitor of caspase-1 in the San-Huang-Xie-Xin-Tang prescription. Coptisine adopted a favorable conformation at the active site of caspase-1. Coptisine significantly attenuated mature interleukin (IL)-1β secretion in RAW264.7 macrophages stimulated with LPS plus ATP, nigericin, or MSU, by blocking caspase-1 activation. Coptisine not only prevented NLRP3 inflammasome assembly by affecting the binding between pro-caspase-1 and apoptosis-associated speck-like protein containing a CARD, but also inhibited inflammasome priming by decreasing NLRP3 expression through inactivation of the nuclear factor-κB pathway. Moreover, coptisine prevented LPS-mediated IL-1β production and MSU-mediated mice paw edema by blocking NLRP3 inflammasome activation in vivo . Coptisine blocks NLRP3 inflammasome activation by inhibiting caspase-1 and may be useful for treating NLRP3 inflammasome-involved gouty arthritis.